Pengembangan Inventori Resiliensi Mahasiswa Bimbingan dan Konseling Islam Institut Agama Islam Negeri Tulungagung - Muhammad Sholihuddin Zuhdi (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This article focuses on the study room of the student of Islamic Guidance and Counseling Students IAIN Tulungagung. The approach used in this study is a quantitative approach, using descriptive analysis methods. Adolescence is a period of storm and stress, a period in which teenagers are turbulent and contain conflicts and mood swings. These developments will enter early adulthood, which requires major changes in thinking and acting, from which independence is the most important thing to become the basis for further developments. Every student has different ways to deal with existing stressors. Individuals who are able to survive certainly have an attitude in dealing with stress so that each student must be able to become resilient. Resilience is very important to develop in students, so an instrument is also needed to determine the level of student resilience, because so far the counselor in particular does not yet have a measure of resilience as the first step in developing student resilience. The results of the research are: 1). Inventory Resilience is very easy to use because there are clear instructions in the process, 2). Based on the assessment of content experts from inventory Resilience developed according to the conditions of Islamic Guidance and Counseling Students IAIN Tulungagung, 3). Based on the small group test shows that inventory resilience is well received by students, 4). Inventory Resilience has limitations and weaknesses that still need further improvement and development.